HUMAN BODY ANTHROPOMORPHIC PHANTOM UTILISATION FOR THE COMPLEX TESTING OF RADIATION THERAPY TECHNOLOGICAL PROCESS - Y. I. Holdman; E. V. Titovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The rapid development of technologies in the field of radiation therapy allows us nowadays to implement precision and most clinically effective radiotherapy techniques for oncological patient’s treatment to minimize the irradiation of normal tissues and improve local tumor control. An important condition for the implementation of the justification principle is strict compliance with the requirements for the accuracy of the dose delivered. High standards of radiation treatments performed are guaranteed by the development and strict compliance with the quality assurance (QA) program in the radiological department. However, due to QA programmes specificity, standardized and worldwide used tests included in the quality management system are trivial mechanical and dosimetric tests that can’t define the presence and magnitude of the integral error in the dose delivered to the patient, which arises as a result of the execution of sophisticated radiation therapy procedures, as well as to take into account the complexity of the implementation of modern methods of treatment. The aim of the work is to develop a method of complex dosimetric testing of the radiation therapy process (end-to-end audit), based on the utilization of the anthropomorphic phantom of the original design. The result of this work is the creation of the modified anthropomorphic phantom for precision dosimetric measurements, designed for testing the following technological procedures of the radiation therapy process: a computer tomography acquisition; a computerized treatment planning system, including a contouring module and dose distribution calculation algorithm; imaging systems integrated with radiation treatment units; dosimetric and technical characteristics of the radiation treatment units. Regular dosimetric testing of the radiation therapy technological process (end-to-end audit) with utilization of the technique proposed by the authors, based on the developed anthropomorphic phantom usage, will allow to assess the accuracy of dose distribution delivered to patients with all major malignant tumors localizations.